Cécile – starsza siostra Effi Briest - Pacholski, Jan (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2019)
This paper deals with Theodor Fontane’s novel Cecile published in 1886. This novel is the first part of the unofficial trilogy of the so-called Berlin novels, which also include Irrungen, Wirrungen (Trials and Tribulations, On Tangled Paths) and Stine. Among these three novels, Cecile is the only one which has not been translated into Polish. In each of these novels, the central motif is misalliance, which in two cases (Cecile and Stine) leads to a tragic end. The motif of a duel, in turn, in which the husband kills the lover or the admirer of the heroine links Cecile to Effi Briest – the most famous of Theodor Fontane’s works. This article attempts to interpret the novel in the context of the similarities between Cecile and Emma Bovary, the protagonist of the masterpiece by Gustave Flaubert and from the perspective of bovarysme –a term coined by Jules de Gaultier. In the analysis, what is important is not only the characterization of Cecile as a character but also the discussion of the role of a letter in the plot of the novel, a letter being a motif used by Fontane in an interesting and surprising way.